Enhancing Natural Killer Cell-Mediated Cancer Immunotherapy by the Biological Macromolecule Nocardia rubra Cell-Wall Skeleton - Jie Wu; Baojun He; Miao Miao; Xibin Han; Hongyan Dai; Heng Dou; Yanqiu Li; Xiaoqing Zhang; Guangchuan Wang (Frontiers Media S.A., 2022)
The biological macromolecule Nocardia rubra cell-wall skeleton (Nr-CWS) has well-established immune-stimulating and anti-tumor activities. However, the role of Nr-CWS on natural killer (NK) cells remains unclear. Here, we explore the function and related mechanisms of Nr-CWS on NK cells. Using a tumor-bearing model, we show that Nr-CWS has slightly effect on solid tumor. In addition, using a tumor metastasis model, we show that Nr-CWS suppresses the lung metastasis induced by B16F10 melanoma cells in mice, which indicates that Nr-CWS may up-regulate the function of NK cells. Further investigation demonstrated that Nr-CWS can increase the expression of TRAIL and FasL on spleen NK cells from Nr-CWS treated B16F10 tumor metastasis mice. The spleen index and serum levels of TNF-α, IFN-γ, and IL-2 in B16F10 tumor metastasis mice treated with Nr-CWS were significantly increased. In vitro, the studies using purified or sorted NK cells revealed that Nr-CWS increases the expression of CD69, TRAIL, and FasL, decreases the expression of CD27, and enhances NK cell cytotoxicity. The intracellular expression of IFN-γ, TNF-α, perforin (prf), granzyme-B (GrzB), and secreted TNF-α, IFN-γ, IL-6 of the cultured NK cells were significantly increased after treatment with Nr-CWS. Overall, the findings indicate that Nr-CWS could suppress the lung metastasis induced by B16F10 melanoma cells, which may be exerted through its effect on NK cells by promoting NK cell terminal differentiation (CD27lowCD11bhigh), and up-regulating the production of cytokines and cytotoxic molecules.